Peningkatan Kemampuan Membaca Permulaan Menggunakan Model Discovery Learning Pada Peserta Didik Disabilitas Daksa Kelas 1 - Aston Abraham Simanullang; Nurhastuti Nurhastuti; Mega Iswari; Antoni Tsaputra (Lembaga Riset dan Inovasi Almatani, 2026)
Discovery Learning model for first-grade students with physical disabilities. The research employed a Classroom Action Research (CAR) design conducted at SLB Negeri Pematang Siantar. The research subjects consisted of three first-grade students with physical disabilities, identified as PS, GH, and BH. Based on the initial assessment, the students’ early reading abilities were categorized as low, with achievement percentages of 30% for PS, 30% for GH, and 30% for BH. The study was carried out in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The observation results in Cycle I indicated an improvement in early reading skills, with PS achieving 45%, GH 50%, and BH 40%. Furthermore, a more significant improvement was observed in Cycle II, with achievement percentages increasing to 80% for PS, 80% for GH, and 75% for BH. Data were collected through observation using an early reading skills assessment sheet, while data analysis was conducted using descriptive quantitative techniques by comparing achievement results across cycles. The findings demonstrate that the application of the Discovery Learning model is effective in enhancing early reading skills among first-grade students with physical disabilities. These results indicate that learning activities emphasizing active student engagement in independently discovering concepts can optimally improve motivation, comprehension, and learning outcomes in accordance with the characteristics of students with physical disabilities.